Associations of methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms with genetic susceptibility to rheumatoid arthritis: a meta-analysis. Issue 2 (February 2017) - Cen, Han; Huang, Hua; Zhang, Li-Na; Liu, Li-Ya; Zhou, Li; Xin, Xia-Fei; Zhuo, Ren-Jie
Abstract The aim of our study was to conduct a meta-analysis to assess whether combined evidence shows associations between C677T and A1298C polymorphisms ofmethylenetetrahydrofolate reductase (MTHFR ) and genetic susceptibility to rheumatoid arthritis (RA). A total of 11 articles involving 20 comparisons were included, containing 12 comparisons for theMTHFR C677T polymorphism and 8 comparisons for theMTHFR A1298C polymorphism. Significant evidence was detected for the association of RA susceptibility with theMTHFR C677T polymorphism T allele under allelic contrast and dominant model in Asians (T versus C, OR = 1.300, 95 % CI = 1.104–1.531, p = 0.002; TT + CT versus CC, OR = 1.495, 95 % CI = 1.187–1.882, p = 0.001). Significant association between RA susceptibility and theMTHFR A1298C polymorphism A allele under recessive model was found in the overall meta-analysis (AA versus AC + CC, OR = 1.281, 95 % CI = 1.048–1.565, p = 0.016). Our meta-analysis results demonstrate that theMTHFR C677T polymorphism is involved in the genetic susceptibility of RA in Asians, and theMTHFR A1298C polymorphism is associated with genetic susceptibility to RA in the overall population. Given the paucity of studies, especially in non-Asian populations, further studies with larger sample sizes are required to elucidate the role ofMTHFR polymorphisms in the genetic basis of RA in different ethnic populations.